Impact of the COVID‐19 pandemic on Creutzfeldt–Jakob disease surveillance and patient care in the United Kingdom. (5th January 2022) - Watson, Neil; Kirby, Jack; Kurudzhu, Hatice; Leitch, Margaret; MacKenzie, Janet; Smith‐Bathgate, Blaire; Smith, Colin; Summers, David; Green, Alison J. E.; Pal, Suvankar
Abstract: Background and purpose: Creutzfeldt–Jakob disease (CJD) is lethal and transmissible. We assessed the impact of the COVID‐19 pandemic on UK CJD surveillance. We hypothesized that (i) disruptions prolonged diagnostic latency; (ii) autopsy rates declined; and (iii) COVID‐19 infection negatively affected diagnosis, care, and survival. Methods: We retrospectively investigated the first year of the pandemic, using the preceding year as a comparator, quantifying numbers of individuals assessed by the UK National CJD Research & Surveillance Unit for suspected CJD, time to diagnosis, disease duration, and autopsy rates. We evaluated the impact of COVID‐19 status on diagnosis, care, and survival in CJD. Results: A total of 148 individuals were diagnosed with CJD in the pandemic (from a total of 166 individuals assessed) compared to 141 in the comparator (from 145 assessed). No differences were identified in disease duration or time to diagnosis. Autopsy rates were unchanged. Twenty individuals had COVID‐19; 60% were symptomatic, and 10% had severe disease. Disruptions in diagnosis and care were frequently identified. Forty percent of COVID‐19‐positive individuals died; however, COVID‐19 status did not significantly alter survival duration in CJD. Conclusions: The COVID‐19 pandemic has not impacted UK CJD case ascertainment or survival, but diagnostic evaluation and clinical care of individuals have been affected. Abstract : This article reports on 2 years of CJD surveillance in the UK, assessing the impact of the pandemic, including COVID‐19 infections and the impact on survival as well as effects on diagnostic services and care.